Modal dispersion characteristics of a single mode metal coated optical waveguide with a guiding region cross-section bounded by two involuted spirals - Pandey P.C.; Pandey B.K.; Ojha S.P. (My University, 2025)
With the use of scalar field approximation we make an analytical study of a metal coated waveguide whose core cross-section is bounded by two spirals of the form 1/r = a θ. This waveguide is similar to that of a distorted slab waveguide in which both a curvature and a flare are present. We derive the modal characteristic equation under the weak guidance approximation. We find only one dispersion curve and this shows that the waveguide is a single mode waveguide, which is a desirable property in waveguides.